Damage Index-Based Lower Bound Structural Design - Mitropoulou, Chara Ch.; Marano, Giuseppe C.; Lagaros, Nikos D. (Frontiers in Built Environment, 2018)
The scope of the work is to detect the most appropriate damage index, able to provide a reliable description of the structural damage level. This damage index is used to formulate a performance-based design framework to be used as a design tool for achieving safer and more economic designs. This objective is achieved by comparing alternative structural systems that comply with the design demands in the most cost-efficient approach, i.e. those requiring less material volume for concrete and steel reinforcement. In this direction, design optimization problems for structural systems are defined for each damage index under consideration and the structural optimization problems at hand are solved by means of a popular metaheuristic search algorithm.